Optimal provision of hydroelectric power under environmental and regulatory constraints. - Edwards, Brian K.; Flaim, Silvio J.; Howitt, Richard E. (Land Economics, 1999)
Hydroelectric power plants can quickly and inexpensively respond to changes in electricity demand. However, this operational flexibility can cause negative environmental impacts and these environmental effects are mitigated through direct restrictions on hydropower operations, rather than taxes or other market-based mechanisms. A dynamic model of hydroelectric generation is used to derive hourly hydroelectric generation and purchases of replacement power to meet contract demand in the presence of these operational restrictions. The pattern of hydropower generation is shown to depend on differences between on-peak and off-peak spot electricity prices within the operational restrictions set by external regulatory mechanisms. (JEL Q25, Q28, Q4) Reprinted by permission of the publisher.